Challenges and Survival Strategies for Women in Small Scale Catering Business: A Case Study of Siyaso Magaba, Mbare - Zinyemba, Alice Z; Changamire, Tatenda (International Journal of Business, Economics and Management, 2014)
Small businesses in the informal sector are increasingly being recognized as generating meaningful and sustainable employment opportunities for women in Zimbabwe. However, women operating small business face many challenges that negatively impact on the viability of those businesses. In order to mitigate those challenges women in small catering business at Siyaso Magaba home industrial area in Mbare Township in Harare (simply known as Siyaso), employ a number of strategies that enable them to survive and continue operating. This paper presents findings from a research carried out at Siyaso to identify those challenges and survival strategies. The challenges include lack of funding, lack of business management skills, stiff competition, stringent requirements for registering a business, defaulting customers and difficulties in balancing work and domestic commitments. These are the challenges that informal business operators have to grapple with in Zimbabwe in general. Over and above these challenges women at Siyaso also face specific challenges that include poor infrastructure in the business area, unaffordable rentals and lack of basic amenities. In order for the women operating catering business at Siyaso to survive they apply a number of strategies which include borrowing money from relatives at no interest being charged, taking turns to give each member an agreed amount of money every month, purchasing s applies on a daily basis instead of buying in bulk, purchasing food items on credit, borrowing from loan sharks and serving extras to clients as a way of luring them from competition. The study concludes by suggesting that in order for the businesses to improve their performance the women should form themselves into a cooperative and register it. They should continue offering a wide variety of meals to customers so as to compete better. The Harare City Council should establish more premises which can be rented at affordable rates from which women can conduct their catering businesses. The city council should also improve amenities at Siyaso Magaba home industrial area.